2009
DOI: 10.1016/j.juro.2009.01.111
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Complex Cystic Renal Mass Using Multiphase Computerized Tomography

Abstract: In cases of complex cystic renal masses diagnostic accuracy can be improved to differentiate renal cell carcinoma by combining Bosniak class and enhancement differences measured on multiphase computerized tomography between precontrast and maximal enhancement phases. This would help determine the need for and the method of surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 11 publications
1
38
0
1
Order By: Relevance
“…11,12,15,[23][24][25][26][27]31,33,34,39,40,42,43,47,51,59 However, the literature is thought to overestimate the true risk of malignancy among category II cysts, as the majority were managed conservatively or had features that made them too complex to be categorized as a Bosniak II cyst. 6,12,26,29,31,32,35,38,59 Importantly, even if malignant, most behave in a relatively benign fashion.…”
Section: Bosniak Category IImentioning
confidence: 99%
“…11,12,15,[23][24][25][26][27]31,33,34,39,40,42,43,47,51,59 However, the literature is thought to overestimate the true risk of malignancy among category II cysts, as the majority were managed conservatively or had features that made them too complex to be categorized as a Bosniak II cyst. 6,12,26,29,31,32,35,38,59 Importantly, even if malignant, most behave in a relatively benign fashion.…”
Section: Bosniak Category IImentioning
confidence: 99%
“…Segmental dysplasia is similar to multicystic dysplastic kidney but is segmental in distribution. 6,7 Gross hydronephrosis can cause severe thinning of the renal parenchyma, which mimics multiple cysts especially on ultrasound, however continuity of the calyces can be traced to the renal pelvis, the pelvis is also dilated. There is severe cortical thinning.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, most retrospective, have evaluated the effectiveness of the Bosniak classification (11-15) . A recent metaanalysis that included nine studies with at least 30 cases each (16) showed that the inclusion of the category II-F led to a reduction of the number of cases included in category III and, consequently, to a decrease in the number of surgical exploration of benign lesions.…”
Section: Validation and Controversiesmentioning
confidence: 99%